Acupuncture Treatment for Patients with Musculoskeletal Disorders and Low Back Pain at the MCO Ladies Clinic in Bekasi - Dwi Permatasari Siregar; Mayang Wulandari; Amal Prihatono (Journal of World Science, 2026)
Low back pain (LBP) is one of the leading causes of disability worldwide and significantly affects physical function and quality of life. This study aimed to describe the management and clinical outcomes of acupuncture treatment for patients with musculoskeletal low back pain at the MCO Ladies Clinic, Bekasi. This study employed a qualitative case study design involving one participant diagnosed with chronic low back pain. Comprehensive assessments were conducted using the four Traditional Chinese Medicine (TCM) examination methods (Wang, Wen, Wen, and Qie). The participant underwent six acupuncture treatment sessions between May 6 and May 16, 2025. Therapy was administered according to TCM syndrome differentiation using acupuncture points BL23 (Shenshu), BL25 (Dachangshu), GV3 (Yaoyangguan), BL40 (Weizhong), KI3 (Taixi), BL60 (Kunlun), and Ashi points. Data were analyzed descriptively by comparing clinical findings and therapeutic outcomes across treatment sessions. The participant was diagnosed with Kidney Deficiency accompanied by Qi and Blood Stagnation. Progressive clinical improvement was observed throughout the six treatment sessions. Pain intensity decreased from 6 to 1 on the Numeric Rating Scale (NRS), muscle spasms diminished, lumbar range of motion improved, and daily functional activities became easier to perform. No adverse events were reported during therapy. Acupuncture management based on Traditional Chinese Medicine principles demonstrated favorable clinical outcomes in reducing pain, improving lumbar function, and enhancing daily activities in a patient with chronic low back pain. These findings support acupuncture as a promising complementary intervention for managing chronic musculoskeletal low back pain.